DETERMINING THE VIEWPOINTS OF UNIVERSITY STUDENTS TOWARDS WORKING AND WORKING LIFE WITHIN THE SCOPE OF GLOBALIZATION: AN ALBANIA AND TURKEY SAMPLE - Bedir Sala (Fırat University, 2019)
Through the end of the 20th century when borders are removed with globalization and especially capital gained mobility, working life taking the lead, considerable changes were observed in societies’ social structures and their viewpoint towards working. Following globalization, societies which couldn’t interriolise Industry Revolution and fell behind in terms of industrialization, fell under the influence of consuming, hedonist and easy axcessing culture. Consuming without producing or partly producing societies tried to be settled by industry societies and global capital, as a result of the of financial crisis, grew into places in which landing job is difficult. Youngs studying with the aim of getting jobs under better conditions have changed their viewpoints towards working life and their expectations from it in the wake of the socio-economic culture aroused through both negative conditions and globalization. In this research, it is aimed to determine the influence of the developments related with globalization on the university students’ viewpoints towards working life and working in consumer societies (countries) In the present study aiming to determine the viewpoints of university students towards working life and working within the scope of globalization, a questionnaire is applied to university students at different faculties in Albania and Turkey. In this context, the research population is determined as Tiran University, Albania and Sakarya University, Turkey. Sample of the research is comprised of students at Engineering, Literature, Law, Theology and Medical faculties of these universities. In consequence of analyzing the research data, it is observed that puritan (requiring hard work) working understanding and ethic value are accepted in Albania who opened its doors to global world in the end of 20th century while in contrast hedonist (enjoying life) values are more commonly accepted in Turkey which is more developed.